Comparative evaluation of PAR1, GPIb-IX-V, and integrin αIIbβ3 levels in cord and adult platelets - Schlagenhauf, A.; Schweintzger, S.; Birner-Grünberger, R.; Leschnik, B.; Muntean, W. (Hämostaseologie, 2010)
Background: Newborn platelets show hyposensitivity in vitro to many important agonists. However, sensitivity of platelets to these agonists is crucial for a functional clot formation. Nevertheless newborns have an excellent hemostasis. Hence, we examined levels of PAR1 thrombin receptor, GPIb-IX-V (CD42b), and Integrin αIIbβ3 in newborn and adult platelets using Western blot analysis.Materials, methods: Platelets of adult and cord blood were isolated, washed, and lysed. Protein samples were separated by SDS-PAGE and blotted on nitrocellulose membranes. Receptors were visualized using immunodetection and evaluated densitometrically. Statistical analysis was performed using SPSS 16.0. Results: We found significantly lower levels of PAR1-receptors and higher levels of CD42b in newborn platelets as compared to adult platelets. Levels of Integrin αIIbβ3 in newborn platelets were comparable to adult platelets. Conclusion: A lower content of PAR1-receptors explains very well the hyposensitivity of cord platelets to thrombin. Higher levels of CD42b may additionally support the effect of larger more adhesive multimeric vWF in newborn plasma.
Keywords: Newborn haemostasis; platelet receptors; Western blot; thrombin receptor